Analysis of the Influence of Knowledge Sharing, Learning Agility, and Creative Self-Efficacy on Innovative Work Behavior in the Creative Industry - Dita Rachmawati; Tri Endar Susianto; Susatyo Adhi Pramono; Sonya Sidjabat; Apriani Riyanti; Hery Purnomo (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study was conducted to examine the extent to which knowledge sharing, learning agility, and creative self-efficacy influence innovative work behavior among creative industry workers in Indonesia. Using a quantitative approach, data were collected through a survey of 120 purposively selected respondents: active workers in the creative industry, aged 20–40, with at least one year of work experience, and directly involved in the creative process. The analysis showed that the research instrument was valid, reliable, and met all classical statistical assumptions. Both simultaneously and partially, the three variables studied significantly influenced innovative work behavior. These findings not only provide theoretical contributions to the development of studies in organizational behavior and human resource management but also offer practical benefits for company management in the creative sector. The results can serve as a basis for designing more targeted employee development strategies, from building a culture of knowledge sharing, enhancing adaptive learning skills, to strengthening employees' confidence in their creative capacity. With these steps, companies will be better prepared to encourage sustainable innovation and strengthen competitiveness amidst increasingly dynamic industrial competition.